1997
DOI: 10.1046/j.1471-4159.1997.68062469.x
|View full text |Cite
|
Sign up to set email alerts
|

4‐Hydroxynonenal, a Lipid Peroxidation Product, Rapidly Accumulates Following Traumatic Spinal Cord Injury and Inhibits Glutamate Uptake

Abstract: Traumatic injury to the spinal cord initiates a host of pathophysiological events that are secondary to the initial insult. One such event is the accumulation of free radicals that damage lipids, proteins, and nucleic acids. A major reactive product formed following lipid peroxidation is the aldehyde, 4‐hydroxynonenal (HNE), which cross‐links to side chain amino acids and inhibits the function of several key metabolic enzymes. In the present study, we used immunocytochemical and immunoblotting techniques to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(103 citation statements)
references
References 43 publications
5
95
1
2
Order By: Relevance
“…However, subsequent studies using one of the more contemporary rat contusion SCI paradigms and more sensitive immunoblotting of the immunohistochemical assay methods have more completely and specifically defined the time course of LP (4-HNE, acrolein) and protein oxidation (protein carbonyl), and nitration (3-NT) following SCI. The first of these showed a peak increase in 4-HNE immunostaining at 24 h [21] or 48 h [20] after SCI. A more recent and more extended immunoblotting/immunohistochemical time course study in the rat contusion model has confirmed that the increase in 4-HNE occurs as early as 1 h, peaks at 24 h, and remains significantly elevated for at least 7 days [23].…”
Section: Onset and Duration Of Oxidative Damage In The Injured Spinalmentioning
confidence: 96%
See 2 more Smart Citations
“…However, subsequent studies using one of the more contemporary rat contusion SCI paradigms and more sensitive immunoblotting of the immunohistochemical assay methods have more completely and specifically defined the time course of LP (4-HNE, acrolein) and protein oxidation (protein carbonyl), and nitration (3-NT) following SCI. The first of these showed a peak increase in 4-HNE immunostaining at 24 h [21] or 48 h [20] after SCI. A more recent and more extended immunoblotting/immunohistochemical time course study in the rat contusion model has confirmed that the increase in 4-HNE occurs as early as 1 h, peaks at 24 h, and remains significantly elevated for at least 7 days [23].…”
Section: Onset and Duration Of Oxidative Damage In The Injured Spinalmentioning
confidence: 96%
“…Second, free radical mechanisms have been demonstrated to potentiate glutamate release, an effect that is antagonized by free radical scavenging agents [53]. Third, the accumulation of LP products such as 4-HNE in synaptosomal membranes harvested from injured spinal cord tissue is associated with an impairment of synaptosomal glutamate uptake [21]. Additionally, it has been demonstrated in other in vitro studies that induction of LP in synaptosomes [54] or spinal neuronal cultures [55] impairs amino acid uptake mechanisms.…”
Section: Enhancement Of Glutamate-mediated Excitotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…6 ± 8 It is well established that ROS increase signi®cantly following CNS mechanical trauma in live animals. 6,9,10 The inhibition of ROS can provide behavioral and functional recovery following various types of injuries. 1,6,11 Therefore, reducing oxidative stress of the tissue is considered to be a potential target for e ective pharmacological intervention to reduce the secondary neuron damage and enhance overall functional recovery following trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Increased HNE formation has been detected in the brain of patients with Alzheimer disease (25), in the spinal cord following traumatic injury (33), in the plasma of children with autoimmune diseases (14), and in the lungs following ozone exposure (42). HNE exerts broad biological toxicity effects including inhibition of DNA and protein synthesis, modification of low-density lipoprotein, and modulation of gene expression (11).…”
mentioning
confidence: 99%